PERANCANGAN BACKDROP UNTUK PERNIKAHAN MENGGUNAKAN TEKNIK MAKRAME - Mukhlisa Sabilla (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
Mukhlisa Sabilla. C0915029. 2019. Backdrop Design for Wedding using the Macrame Technique. Final Project: Textile Craft Study Program, Faculty of Arts and Design, Sebelas Maret University. “Designing backdrop for wedding using the macrame technique” aims to explore the makame knots made into wedding decorations. The design results into an innovative product and has product differentiation. The realization of the product can add to the visual wealth of macrames that function aswedding decorations. The result of the design is a backdrop for wedding made with macrame techniques by taking the idea of the shape of flora sirih gading leaves and lotus flowers, the form of fauna butterflies, kawung motifs, wjikan, ukel/besusulan, tumpal/sorot and tassels. Backdrop consists of 3 parts, the main part is in themiddle, the complement is on the left and right. Laying the backdrop on a wooden frame inspired by the basic shape of the house. Backdrop with macrame technique offers different nuances in terms of aesthetics and visual appearance.